The Application of Criminal Sanctions for Perpretrators of Sexual Violence Against Children with Disabilities - Cinta Mawar Lintang Dinasti (UM Purwokerto Press, 2023)
Sexual violence against children is one of the new forms of crime, which involves children as the next generation of the nation, so that the crime is quite a concern among the community. Child protection is an effort to create a situation where all children can carry out their obligations and rights. As for the implementation of balance in a society, legal protection should be sought in various aspects of state and social activities. Children with disabilities are often the main target to be used as victims of criminals, discrimination and sexual violence. This can be seen from the increase in criminal cases against women and children with disabilities which tend to increase from year to year. The purpose of this study is to determine the legal protection of children with disabilities as victims of sexual violence and criminal sanctions against perpetrators of sexual violence against children with disabilities. The method used is a normative method along with statutory and conceptual approaches. The results of the study say that legal protection of children as victims of sexual violence is contained in article 1 paragraph (2) of Law No. 35 of 2014 concerning child protection, namely so that the child gets security and his rights as a child. The implementation of good rule enforcement based on proportional guidelines must seek to create an overall balance value, which includes the value of balance by the victim, the criminal, and the people as a whole.